The relationship of proton brand personality and purchase intention with brand attitude as mediator, Kota Kinabalu consumer perspective - Ag. Ahmad Iskandar Abu Bakar (2014)
The purpose of this study is to investigate the influence of brand personality and brand attitude towards purchase intention in the context of purchasing Proton brand which is leading Malaysian car manufacturer. In addition, the mediating effect of brand attitude on the relationship between brand personality and purchase intention, was investigated. The current study has proven no relationship was found between brand personality and purchase intention. However, this study discovered a new dimension identified as "eastern value" which was found based on the behavioral reaction of the respondents in Kota Kinabalu. The data was collected at Proton service center in Kota Kinabalu. The SPSS statistical software was employed in the data analysis. Surprising, the five generic dimensions proposed by Aaker (1997) which are comprise of sincerity, excitement, competence, ruggedness and sophistication were inapplicable in Kota Kinabalu market setting which is established in the current findings. Discussion, limitations and recommendations for future researchers are also presented in this study.